Комплекс електронних навчальних словників ”ГЛОСА” - Перебийніс, В.; Назаров, С.; Бобкова, Т. (Лексикографічний бюлетень, 2006)
Learner’s dictionaries are intended for students and teachers of a foreign language and serve the purpose of selecting and activizing vocabulary to be studied. Lexical minimums are aimed at selecting most frequent words to be taught at different stages of studying a foreignlanguage. They are to help teachers and authors of text-books in determining the syllabus and making the process of teaching more effective.